Dança macabra - Mascarada : contribuições de conservação restauro para uma pintura do acervo da FBAUL - Pacheco, Rui Manuel Malveiro, 1972- (2018)
Dance Macabre, title of attribution of the contemporary oil painting composition dated from 1965 with expressionist features, integrated during the inventory of the Pictorial Collection at Lisbon's University Fine Arts Faculty Painting Repository in 2010. The struggle to decipher the painting's signature has made it difficult for a long time to understand its authorship and origins, leaving the object to neglect for years while a strong repercussion took over its general conservative state, visible through the variety and class of alterations it bears. The multidisciplinary investigation presented in this dissertation as a form of a study in conservation and restoration within contemporary art, aims to reveal a set of answers to the historiographical and conservation restoration concerns that this singular artistic good has raised. For the first time a series of interdisciplinary actions are combined to clarify the authorship of the painting, define its historical-artistic contextualization and the articulation of these aspects within a contribution in conservation restoration guidelines in contemporary art. The painting's attribution to António José Guerra Ferramentas, former painter and student at ESBAL, its categorization as a conclusion thesis for the Complementary Painting Course in 1965 and its thematic disambiguation reinforced the already evident need for a technical and material study of the painting. The action was supported by exams such as Visible Radiation Photograph with Incident, Low and Transmitted Light, Photographic Fluorescence Examination by UV Radiation and Digital Microscopy with Visible and UV Light. The further enrollment of analyses like Energy Dispersive X-Ray Fluorescence (ED-XRF) and micro-Raman spectroscopy (μ-Raman) have enriched the investigation, aiding to the identification of its elemental constitution and composition of its materiality. The joint venture of these methodologies applied to the painting constituted a useful tool for the characterization of the degradation processes installed, providing a diagnosis and allowing the elaboration of a small material contribution. The ED-XRF identified in the yellow, red, green and burgundy regions S, Ca, Ba, Fe, Zn, Hg, Pb and Sr, elements for the molecular characterization of the various pigments, synthetic dyes, filler and impurities in the samplings. The μ-Raman confirmed the monoazo PY (1:1) CI 11680:1, PR (4) CI12085, FcCu PB polymorphs (15:4) CI74160: 4 green shade and PB (15:6) CI 74160: 6 red shade and the molecules of PW (4) CI 77947, PW (21) CI 77120 and PR (101) CI77491. The delineation of an intervention proposal is an incentive to claim the painting back to its original physical-chemical-aesthetic balance and fosters the will to advertise the artistic creation of a very relevant figure within the Portuguese Contemporary Art World of the late twentieth century, awaiting to be rediscovered and still soughing for a meritorious recognition